2009
DOI: 10.1523/jneurosci.5773-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Lactate Release and Promotion of Cortical Arousal during Prolonged Waking Is Attenuated in Aging

Abstract: The wake-promoting basal forebrain (BF) is critically involved in sustaining cortical arousal. In the present study, we investigated how aging affects the capacity of the BF to cope with continuous activation during prolonged waking. Increased neuronal activity induces lactate release in the activated brain area, and BF stimulation increases cortical arousal. We used in vivo microdialysis to measure lactate levels in the BF, and electroencephalography (EEG) to measure cortical arousal, during 3 h sleep depriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 76 publications
2
18
1
Order By: Relevance
“…7A), and two peaks in the delta and theta ranges during wake (Fig. 7B), consistent with previous reports (44,64,65).…”
Section: Baseline Sleepsupporting
confidence: 92%
“…7A), and two peaks in the delta and theta ranges during wake (Fig. 7B), consistent with previous reports (44,64,65).…”
Section: Baseline Sleepsupporting
confidence: 92%
“…Changes in metabolic demand would therefore reflect the homeostatic sleep process with prolonged wakefulness consuming excessively energy. This was demonstrated by studies showing that (i) cortical neurones increase firing in the course of waking ) and (ii) that this increase in cortical activity during waking is paralleled by increases in the brain's lactate level (Urrila et al 2003, Wigren et al 2009, Dash et al 2012. Also, many of the genes involved in energy metabolism and synaptic potentiation are upregulated during waking .…”
Section: Energy Metabolism-related Theoriesmentioning
confidence: 96%
“…Whether this reflects reduced build-up of homeostatic sleep pressure with ageing, reduced ability to sleep or problems producing slow waves, is currently not known (Dijk et al 2010). Recent studies suggest, however, that the age-related decrease in SWA is most likely caused by reduced homeostatic sleep pressure (Duffy et al 2009, Wigren et al 2009, Dijk et al 2010, Rytkonen et al 2010, although the underlying molecular mechanisms are not well understood. The reduction could be due to changes in the homeostatic sleep factors (Duffy et al 2009, Rytkonen et al 2010 or due to reduced synaptic density and connectivity (Carrier et al 2011).…”
Section: Ageingmentioning
confidence: 99%
“…Neuronal projections from the basal forebrain regulate the development and functioning of its target regions, including the cortex (Fahnestock et al, 2002;Wigren et al, 2009;Zant et al, 2012). In the cortex, we found that Bdnf transcripts were induced by SD with more prominent changes in Bdnf1 expression: main effect of SD for Bdnf1 F 1,28 = 26.56, P < 0.0001, for Bdnf4 F 1,28 = 10.47, P = 0.003 and a trend for Bdnf9a F 1,28 = 3.29, P = 0.081 (Fig.…”
Section: Spontaneous Daytime and Sd-induced Changes In Bdnf Methylatimentioning
confidence: 99%